Kejadian Mild Cognitive Impairement pada Petani Tembakau Pengguna Pestisida di Kabupaten Jember - Reny Indrayani; Prehatin Trirahayu Ningrum; Ellyke Ellyke; Isa Marufi; Anita Dewi Moelyaningrum; Ragil Ismi Hartanti; Rahayu Sri Pujiati; Kurnia Ardiansyah Akbar; Globila Nurika; Ana Islamiyah Syamila (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Mild Cognitive Impairment (MCI) is a prodromal phase of cognitive decline that can precede the emergence of Alzheimer's Disease (AD). The populations most at risk are farmers who apply pesticides to their crops. The purpose of this study was to analyze the relationship between age, length of working, and pesticide use (frequency and duration of spraying) with the incidence of MCI in tobacco farmers in Jember District. The type of this study was observational analytic with cross sectional design. The respondents of this research were 200 farmers in the district area, with stratified sampling method. Data analysis used the chi-square statistical test. The results showed that most respondents were aged ≥ 45 years and most respondents had working period of > 10 years. Most respondents sprayed pesticides 3-4 times in 1 month and the duration of spraying was evenly divided into two groups, ≤ 2 hours and> 2 hours. The results of bivariate analysis showed that in the study respondents, there was no relationship between age, years of working, and frequency of pesticide spraying with MCI, but there was a relationship between the length of pesticide spraying (p = 0,026) with MCI. Based on these results, it is necessary to educate tobacco farmers, especially in Jember Regency about the dangers of pesticides and to shorten the duration of pesticide spraying.